West and the Metanarrative of Terrorism: A Genealogical Analysis and the Absurdity of the U.S. Terrorism Narrative in the Middle East - Mas'odi, Mas'odi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
This research will examine the Western world's metanarrative regarding the issue of terrorism and its impact on the Eastern world, especially the Middle East region. Terrorism is a complex issue and often becomes absurd when used as a political narrative by the ruling elites of the Western world. The West often enters the arena of war in the Middle East and carries out proxy wars against other opposing powers. The West, especially the US, often blurs the facts about who the perpetrators and victims of terrorism are. This research uses qualitative research methods to describe the phenomenon and discourse of terrorism developing in the Middle East. This research uses Pierre Boudieu's theory of genetic structuralism as an analytical tool. From this research, it was found that there was injustice in the West, especially the US, in using the narrative of terrorism. The US also uses violent methods to carry out counter-terrorism, which only gives rise to new terrorists emerging